A method for comprehensive utilization of biochemical sludge and its resource utilization
By refluxing the biochemical sludge with concentrated sulfuric acid and combining ammonia water to adjust the pH value, the problems of long reaction time, high cost and serious pollution in biochemical sludge treatment are solved, and the production of high-purity ammonium aluminum sulfate and pyrite is achieved, with low cost and environmental protection.
Patent Information
- Application Number
- CN202210800666.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-07-08
AI Technical Summary
In the prior art, biochemical sludge treatment has problems such as long reaction time, high cost and serious reaction pollution, and the flue gas pollution and heat loss caused by sludge incineration limit its application.
The biochemical sludge was refluxed with 98% concentrated sulfuric acid at a specific temperature to form a black suspension, and then filtration through a quartz sand funnel to obtain an organic matter and sulfuric acid solution. The pH value was further adjusted by ammonia water, and flocs were generated and dried, and finally calcined for XPS and XRD tests.
Effective separation and purification of metal elements in biochemical sludge was achieved, and high-purity ammonium aluminum sulfate and pyrite were produced, which reduced production costs and had good safety and environmental protection performance in the process.
Smart Images

Figure CN115893801B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sludge resource treatment, in particular to a method for comprehensive utilization of biochemical sludge and its resource utilization. Background Art
[0002] With the continuous development of social economy, more and more sewage is generated by chemical industry (coal chemical industry, petrochemical industry), printing and dyeing papermaking industry, and urban life. When treating these sewage, a large amount of biochemical sludge will be produced. It is a major technical problem in the fields of energy conservation, environmental protection and various industrial production to establish an economical, efficient, energy-saving and environmentally friendly biochemical sludge treatment method, and it is best to achieve resource recycling at the same time to achieve the requirements of harmless treatment and resource utilization of sludge.
[0003] According to incomplete statistics, my country currently produces 300,000 tons of biochemical sludge annually. The sludge not only contains a large number of toxic and harmful substances such as parasite eggs, pathogenic microorganisms and heavy metal ions, but also emits a foul odor. If these biochemical sludges are not properly treated, they will cause serious secondary pollution. At present, the main methods for treating sludge in my country are landfill treatment, direct utilization and incineration. Biochemical sludge contains a large number of harmful substances such as heavy metals. Direct landfill will seriously pollute soil and groundwater resources. The proportion of biochemical sludge in my country's groundwater quality is as high as 60%. The high organic matter content in biochemical sludge is not conducive to the growth of crops, so it cannot be directly used in the land. In addition, the moisture content of biochemical sludge is generally above 95%, and even after mechanical dehydration, it can be as high as 70% to 85%. Usually, most of the water in the sludge is removed by infiltration or evaporation, and then mechanically dried and incinerated. The volume of the sludge is greatly reduced after incineration, which can solve the problem of landfill. In addition, the device is costly and energy-intensive. The flue gas pollution, heat loss and waste residue generated during the incineration process also require corresponding post-treatment measures. Therefore, the incineration treatment is greatly restricted, so the treatment problem of biochemical sludge has not been well solved. Summary of the invention
[0004] The purpose of the present invention is to provide a method for comprehensive utilization of biochemical sludge and its resource recovery, which solves the problems of long reaction time, high cost and serious reaction pollution in the prior art.
[0005] The technical solution adopted by the present invention is a method for comprehensive utilization of biochemical sludge and its resource utilization, which specifically includes the following steps:
[0006] 1) Add the biochemical sludge into the reactor, then add 12.5-80 mL of 98% concentrated sulfuric acid, prepare a reflux condenser, reflux at a certain temperature for 2-2.5 hours under magnetic stirring, and cool naturally to room temperature after the reflux to obtain a black suspension;
[0007] 2) The product suspension obtained in the previous step is filtered through a quartz sand funnel, and the obtained insoluble solid is the organic matter in the waste residue, which is collected separately for later use;
[0008] 3) Under the premise of real-time monitoring of the solution pH = 4-8.5, add ammonia water to the filtrate obtained in the previous step, and the solution will produce a large amount of flocs. The large amount of flocs produced are filtered and dried for 2-3 hours. The obtained solid is calcined and then tested by XPS and XRD;
[0009] 4) Evaporate the filtrate to dryness and detect the solute.
[0010] The present invention is further improved in that:
[0011] In step 1), 50 g of water-containing biochemical sludge is taken and dried at 150° C. for 3 hours before use.
[0012] In step 1), the reflux temperature is 120-125°C.
[0013] In step 1), the reflux time is 2 to 2.5 hours.
[0014] In step 2), the filtrate may be a sulfuric acid solution.
[0015] In step 3), the commercially available ammonia water is 30 wt.%.
[0016] In step 3), the pH is adjusted to 4-8.5.
[0017] In step 4), the drying time is 2 to 3 hours.
[0018] Beneficial effects of the present invention:
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The present invention provides a method for comprehensive utilization of biochemical sludge and its resource recovery, which can convert Al in biochemical sludge into 3+ Complete leaching, the Fe element remains in the organic matter in the form of ferrocyanide, which is insoluble in acid, achieving the purpose of metal element separation. By controlling the amount of H2SO4 and ammonia water added, high-purity ammonium aluminum sulfate, i.e. fertilizer powder, can be obtained, which has a huge market demand;
[0021] 2) The present invention provides a method for comprehensive utilization of biochemical sludge and its resource utilization, which has low production cost. The method provided by the present invention only requires hydrolysis and repolymerization of ferrous ferric alum (hydrothermal method, completed in one step) to obtain flocculant polyferric sulfate, which can be used repeatedly. Ferrous ferrous ferric alum can also be sold to iron plants for ironmaking or sulfuric acid production. The existing method requires the addition of other auxiliary reagents, which is more expensive;
[0022] 3) The present invention provides a method for comprehensive utilization of biochemical sludge and its resource utilization, which has good safety and green environmental protection performance. The method provided by the present invention is used to resource biochemical sludge, the synthetic raw materials are simple, and no wastewater is discharged during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the full XPS spectrum of biochemical sludge.
[0024] Figure 2 This is the C 1s spectrum of biochemical sludge.
[0025] Figure 3 It is the Fe 2p spectrum of biochemical sludge.
[0026] Figure 4 This is the N 1s spectrum of biochemical sludge.
[0027] Figure 5 This is the XRD spectrum of biochemical sludge (after drying).
[0028] Figure 6 This is the full XPS spectrum of sample A1.
[0029] Figure 7 is the C 1s spectrum of sample A1.
[0030] Figure 8 is the XRD spectrum of sample A1.
[0031] Fig. 9 This is the full XPS spectrum of sample A2.
[0032] Fig.10 is the C 1s spectrum of sample A2.
[0033] Fig.11 is the XRD spectrum of sample A2.
[0034] Fig.12 This is the full XPS spectrum of sample B1.
[0035] Fig.13 is the C 1s spectrum of sample B1.
[0036] Fig.14 is the N 1s spectrum of sample B1.
[0037] Fig.15 is the S 2p spectrum of sample B1.
[0038] Fig.16 is the Fe 2p spectrum of sample B1.
[0039] Fig.17 This is the XRD spectrum of sample B1
[0040] Fig.18 This is the full XPS spectrum of sample B2.
[0041] Fig.19 This is the C 1s spectrum of sample B2.
[0042] Fig. 20 is the N 1s spectrum of sample B2.
[0043] Fig.21 is the S 2p spectrum of sample B2.
[0044] Fig. 22 is the XRD spectrum of sample B2.
[0045] Fig.23 This is the full XPS spectrum of sample B3.
[0046] Fig.24 This is the C 1s spectrum of sample B3.
[0047] Fig.25 is the N 1s spectrum of sample B3.
[0048] Fig.26 is the S 2p spectrum of sample B3. DETAILED DESCRIPTION
[0049] The present invention comprises the following steps:
[0050] 1) Add 50 g of water-containing biochemical sludge into a reactor, then add 12.5 mL of 98% concentrated sulfuric acid, prepare a reflux condenser, and then heat to 120° C. under magnetic stirring, reflux at this temperature for 2 hours and naturally cool to room temperature to obtain a black suspension;
[0051] 2) The suspension obtained in the previous step is filtered through a quartz sand funnel (the filter paper will be burned by sulfuric acid). The insoluble solid (black) obtained is the organic matter in the waste residue, which is collected separately for later use. The filtrate is a sulfuric acid solution of iron sulfate and aluminum sulfate (light black), and also contains a very small amount of calcium salt and phosphate salt;
[0052] 3) Under the premise of real-time monitoring of the pH value of the solution, ammonia water (30 wt.%) was added dropwise to the filtrate obtained in the previous step to adjust the pH to 4. At this time, a large amount of floccules were generated in the solution. The large amount of floccules were filtered out, and the obtained solid was calcined and then subjected to XPS and XRD tests;
[0053] 4) The filtrate from the previous step is evaporated to dryness and the composition of the solute is detected.
[0054] Example 1
[0055] 1) Add the biochemical sludge (50g of water, first dried in an oven at 150℃ for 3 hours before use) into a 500mL round-bottom flask, then add 80mL of 98% concentrated sulfuric acid (commercially available concentrated sulfuric acid), prepare a reflux condenser, and heat to 120℃ under magnetic stirring. Reflux at 120℃ for 2 hours (concentrated sulfuric acid can reflux at 120℃). The color of the suspension is blue-black, and it is naturally cooled to room temperature;
[0056] 2) The suspension obtained in the previous step is filtered through a quartz sand funnel (the filter paper will be burned by sulfuric acid). The insoluble solid obtained is the organic matter in the waste residue, which is collected separately and set aside (can be used for charring in the future). The filtrate may be a sulfuric acid solution of iron sulfate, aluminum sulfate, zinc sulfate (yellow-brown, black, dark color), or contain very small amounts of calcium salts and phosphate salts;
[0057] 3) Under the premise of real-time monitoring of the pH value of the solution (detected by pH test paper), commercially available ammonia water (30 wt.%) was added dropwise to the filtrate obtained in the previous step until pH = 3, at which time a very small amount of black precipitate appeared in the solution. Ammonia water was continuously added dropwise until pH = 4, at which time a large amount of black-red floccules were produced. The solid was filtered and dried for 2 hours. The obtained solid (sample A1, 1.25 g) was subjected to XPS and XRD tests;
[0058] 4) The filtrate was evaporated to dryness, and the composition of the solute (sample A2, 101.88 g) was detected, and XPS and XRD tests were performed.
[0059] Example 2
[0060] 1) Add the biochemical sludge (50 g of water, first dried in an oven at 150°C for 3 hours before use) into a large porcelain crucible, then add 25 g (12.5 mL) of 98% concentrated sulfuric acid (commercially available 98% concentrated sulfuric acid), stir evenly with a glass rod, then put into a muffle furnace, heat to 280°C, roast for 3 hours, then naturally cool to room temperature to obtain a black solid, add 150 mL of tap water to the above roasted solid (containing concentrated sulfuric acid), then heat to 125°C under magnetic stirring, reflux at this temperature for 2.5 hours (concentrated sulfuric acid can reflux at 125°C), the color of the suspension is bluish black, and naturally cool to room temperature;
[0061] 2) The suspension obtained in the previous step is filtered through a quartz sand funnel (the filter paper will be burned by sulfuric acid). The insoluble solid (black) obtained is the organic matter in the waste residue, which is collected separately for later use (sample B1, 3.78g, characterized by XPS and XRD). The filtrate is a sulfuric acid solution of iron sulfate and aluminum sulfate (light black), and also contains a very small amount of calcium salt and phosphate salt;
[0062] 3) Add commercially available ammonia water (30 wt.%) dropwise to the aqueous phase of the previous step until the pH reaches 8.5, at which time a large amount of red-brown flocculent precipitates are produced. The solid is filtered and dried for 3 hours to obtain a red-brown solid (i.e., sample B2, 2.21 g, characterized by XPS and XRD).
[0063] 4) The filtrate from the previous step was evaporated to dryness, and the composition of the solute was detected (sample B3, 3.27 g, characterized by XPS and XRD).
[0064] Based on the above embodiments and the accompanying drawings:
[0065] like Figure 2 As shown by Figure 2 It can be seen that in addition to O, C, N, F, Na, Fe, Cl, and S, biochemical sludge also contains Al (due to the relatively large content of organic matter, Al is not included in the statistics of the software, but it does contain this element).
[0066] Depend on Figure 3 It can be seen that the peak at 284.3 eV represents unsaturated carbon (such as C in benzene or fused ring compounds, with a hybridization mode of sp 2 ), the peak with binding energy at 285.7 eV represents the carbon of CO bond (not excluding components containing CN or C=N bonds), and the peak with binding energy at 288.2 eV represents the carbon of carboxyl group. The molar ratio of the three is, sp 2 Carbon: Carbon of CO bond: Carbon of carboxyl group = 49.78: 40.50: 9.72. It can be seen that the organic components contained in biochemical sludge should be small organic molecules containing C, O, and N (because there is no peak after 290eV, the organic components do not contain carbon chains in polymer form, such as polyethylene and polypropylene).
[0067] Depend on Figure 4 It can be seen that the peak of binding energy at 726.0 eV represents Fe 2p 1 / 2 photoelectrons, while the peak at 712.8 eV represents Fe 2p 3 / 2 Photoelectrons, the above peak positions all represent Fe 3+ , that is, the Fe element in biochemical sludge is Fe 3+ exists in the form of Fe 2+ The existence of Fe 2+ Fe 2p 1 / 2 The photoelectron peaks at around 721.0 eV, and its Fe 2p 3 / 2 The photoelectron peaks at around 708.0 eV.
[0068] Depend on Figure 5It can be seen that the N1s spectrum of biochemical sludge contains two parts: the peak with binding energy at 399.7eV represents the -NH- group, which comes from the organic components; the peak with binding energy at 401.6eV represents the amino or tertiary amine group, which comes from the organic components. No peak with binding energy at 405-407eV was found, indicating that the biochemical sludge does not contain NO3 - .
[0069] Depend on Figure 6 It can be seen that the biochemical sludge after drying does not show obvious diffraction peaks, which may be because the sludge has a cross-linked structure and the diffraction signal is very weak.
[0070] Depend on Figure 8 It can be seen that sample A1 contains O, C, N, Cl, and S, but no other impurity elements.
[0071] Depend on Fig. 9 It can be seen that the peak at 284.6 eV represents unsaturated carbon (such as C in benzene or condensed ring compounds, with a hybridization mode of sp 2 ), the peak with binding energy at 285.8 eV represents the carbon of CO bond (not excluding components containing CN or C=N bonds), and the peak with binding energy at 288.5 eV represents the carbon of carboxyl group. The molar ratio of the three is, sp 2 Carbon: Carbon of CO bond: Carbon of carboxyl group = 51.95: 37.26: 10.79. It can be seen that the organic component contained in sample A1 should be an organic small molecule containing C, O, and N (because there is no peak after 290eV, the organic component does not contain carbon chains in polymer form, such as polyethylene, polypropylene, etc.).
[0072] If Fig.10 It can be seen that the main component of sample A1 is ammonium aluminum sulfate (NH4Al(SO4)2, PDF No. 23-0001). In addition, the small peak at 2θ=20-24° represents a small amount of impurities of other aluminum salts or oxides.
[0073] like Fig.12 As shown, sample A2 contains not only O, C, N, F, and S elements, but also Fe element.
[0074] Depend on Fig.13 It can be seen that the peak at 284.8 eV represents saturated carbon (such as C in alkyl, with a hybridization mode of sp 3 ), the peak with binding energy at 286.3 eV represents carbon with CO bond (not excluding components with CN or C=N bond), the peak with binding energy at 289.0 eV represents carbon with carboxyl group, and the carbon with binding energy at 292.5 eV represents carbon in polymer form, such as polyethylene and polypropylene. The molar ratio of the four is, sp 3Carbon: Carbon in CO bond: Carbon in carboxyl group: Carbon in polymer form = 42.81: 35.66: 15.35: 6.17. It can be seen that the organic components contained in sample A2 should be small organic molecules containing C, O, N and a small amount of polymers.
[0075] Depend on Fig.14 It can be seen that sample A2 is ammonium sulfate ((NH4)2SO4, PDF No.72-0456) with a higher purity.
[0076] The first round of experiments found that Al can be extracted with sulfuric acid and ammonia, and Fe is likely to remain in the organic matter and not enter the solution. Given the selling prices of sulfuric acid (800 RMB / ton) and ammonia (1000 RMB / ton), the use of sulfuric acid and ammonia needs to be further reduced. In addition, if the calcination temperature is 400°C, the energy consumption is high, and it is necessary to consider ways to use the product as a resource without calcination.
[0077] Depend on Fig.16 It can be seen that sample B1 contains O, C, N, Fe, and S, but no other impurity elements.
[0078] Depend on Fig.17 It can be seen that the peak at 284.3 eV represents unsaturated carbon (such as phenyl or C of carbon-carbon double bond, with hybridization mode of sp 2 ), the peak with binding energy at 285.5 eV represents the carbon of CO bond (not excluding components containing CN or C=N bonds), and the peak with binding energy at 288.3 eV represents the carbon of carboxyl group. The molar ratio of the three is, sp 2 Carbon: Carbon of CO bond: Carbon of carboxyl group = 41.84: 44.94: 13.22. It can be seen that the organic components contained in sample B1 should be small organic molecules containing C, O, and N.
[0079] Depend on Fig.18 It can be seen that the N1s spectrum of sample B1 contains two parts: the peak with a binding energy of 399.0 eV represents the -NH- group, which originates from the organic component; the peak with a binding energy of 400.7 eV represents the amino or tertiary amine group, which originates from the organic component. No peak with a binding energy of 405-407 eV was found, indicating that sample B1 does not contain NO3 - .
[0080] Depend on Fig.19 It can be seen that the peak at 169.0 eV represents the S 2p photoelectron of sample B1. According to its peak position, it is judged that the S at this location is SO4 2- The peak at the binding energy of 163.8 eV also represents the S 2p photoelectron of sample B1. According to its peak position, it is judged that the S there exists in the form of sulfonic acid group or organic sulfur.
[0081] Depend on Fig. 20 It can be seen that the peak of binding energy at 726.0 eV represents Fe 2p 1 / 2 photoelectrons, while the peak at 712.8 eV represents Fe 2p 3 / 2 Photoelectrons, the above peak positions all represent Fe 3+ , that is, the Fe element in sample B1 is Fe 3+ exists in the form of Fe 2+ The existence of Fe 2+ Fe 2p 1 / 2 The photoelectron peaks at around 721.0 eV, and its Fe 2p 3 / 2 The photoelectron peaks at around 708.0 eV.
[0082] Depend on Fig.21 It can be seen that the main component of sample B1 is ferrous iron alum, in addition, it also contains a very small amount of hydrated iron sulfate. Ferrous iron alum and hydrated iron sulfate are derived from polyferric sulfate (a flocculant for producing biochemical sludge), which can be treated by simple chemical methods to regenerate polyferric sulfate, or directly sold to iron plants for ironmaking.
[0083] Depend on Fig.23 It can be seen that sample B2 contains not only O, C, N, and S, but also Al.
[0084] Depend on Fig.24 It can be seen that the peak at 284.6 eV represents saturated carbon (such as alkyl carbon, hybridization mode is sp 3 ), the peak with binding energy at 285.9 eV represents the carbon of CO bond (components containing CN or C=N bonds are not excluded), and the peak with binding energy at 288.7 eV represents the carbon of carboxyl group. The molar ratio of the three is, sp 3 Carbon: Carbon of CO bond: Carbon of carboxyl group = 57.41: 32.96: 9.63. It can be seen that the organic components contained in sample B2 should be small organic molecules containing C, O, and N.
[0085] Depend on Fig.25 It can be seen that the N1s spectrum of sample B2 contains a part: the peak of binding energy at 401.3 eV represents NH4 + No peaks with binding energy of 405-407 eV were found, indicating that sample B2 does not contain NO3 - .
[0086] Depend on Fig.26 It can be seen that the peak of binding energy at 169.2 eV represents the S 2p of sample B2. 1 / 2 Photoelectron, the peak at 168.1eV represents the S 2p of sample B2 3 / 2 Photoelectrons. According to the S 2p of sample B23 / 2 The peak position of the photoelectron indicates that the S in sample 1 is in the form of SO4 2- Form exists.
[0087] The main component of sample B2 is ammonium aluminum sulfate (NH4Al(SO4)2. In addition, it also contains a small amount of aluminum sulfate.
[0088] In addition to O, C, N, Na, S, and Al, no other impurity elements were found in sample B3.
[0089] The peak at 284.7 eV represents saturated carbon (such as alkyl carbon, with a hybridization mode of sp 3 ), the peak with binding energy at 286.0 eV represents the carbon of CO bond (not excluding components containing CN or C=N bonds), and the peak with binding energy at 288.7 eV represents the carbon of carboxyl group. The molar ratio of the three is, sp 3 Carbon: Carbon of CO bond: Carbon of carboxyl group = 52.28: 38.58: 9.15. It can be seen that the organic components contained in sample B3 should be small organic molecules containing C, O, and N.
[0090] The N1s spectrum of sample B3 contains one part: the peak of binding energy at 401.4 eV represents NH4 + No peak with binding energy of 405-407 eV was found, indicating that sample B3 does not contain NO3 - .
[0091] The peak at 169.3 eV represents the S 2p of sample B3. 1 / 2 Photoelectron, the peak at 168.2eV represents the S 2p of sample B3 3 / 2 Photoelectrons. According to the S 2p of sample B3 3 / 2 The peak position of the photoelectron indicates that the S in sample 1 is in the form of SO4 2- Form exists.
Claims
1. A method for comprehensive utilization of biochemical sludge and its resource utilization, characterized in that: The specific steps include: 1) Add the biochemical sludge into the reactor, take 50g of the water-containing biochemical sludge, dry it at 150℃ for 3 hours before use, then add 12.5-80mL of 98% concentrated sulfuric acid, prepare a reflux condenser, reflux at 120-125℃ for 2-2.5h under magnetic stirring, and reflux until the reflux is finished, cool it naturally to room temperature to obtain a black suspension; 2) The product suspension obtained in the previous step is filtered through a quartz sand funnel, and the obtained insoluble solid is the organic matter in the waste residue, which is collected separately for later use; 3) Under the premise of real-time monitoring of the solution pH = 4-8.5, add ammonia water to the filtrate obtained in the previous step, and the solution will produce a large amount of flocs. The large amount of flocs produced are filtered and dried for 2-3 hours. The obtained solid is calcined and then tested by XPS and XRD; the ammonia water is commercially available at 30wt.%; 4) Evaporate the filtrate to dryness and detect the solute.
Citation Information
Patent Citations
Method for utilizing sewage precipitates of plants for biological purification
RU2109696C1